Phishing as a form of fraud identity theft in healthcare: Victimization during COVID-19 pandemic - Vilić Vida (Temida, 2022)
The coronavirus pandemic affects all segments of human life around the world. Due to the risk to people's health, personal communication has been completely changed and most professional activities and contacts must take place in a cyber environment, with the help of computers and mobile telephony. On-line communication and the use of social networks undoubtedly represent a conditio sine qua non in a situation when compliance with numerous preventive measures are required, including the work from home, online teaching in schools, a ban on gatherings etc. The positive aspects of this kind of communication are undoubtedly obvious and necessary, but they also created new forms of victimization due to insecure protocols for sending e-mails, inadequate level of privacy protection, insufficient information security, the existence of so-called security holes and the use of the same devices and digital services for professional and private purposes. Hacking phishing activities during the pandemic mostly endangered the security of confidential data collected within medical information systems, educational institutions, and in the field of banking, when the user is expected to compromise his/her digital identity and publish his/her data. The subject of this paper is the presentation of some of the most common phishing activities and identity theft in the field of health care, provision of health services, procurement of medicines and vaccines against coronavirus, which have been recorded in the world since the beginning of the pandemic. The phishing activities that will be presented in this paper significantly contribute to the further spread of panic from the misuse of medical data of infected persons and their contacts. The paper aims to point out the most common forms of victimization that have appeared around the world, as a consequence of cyber security violations due to hacker attacks during the COVID- 19 pandemic. Special emphasis in the paper is on these “pandemic” cyber dangers, as well as on the mechanisms for avoiding this type of victimization.